Long‐Term Results After Single and Multiple Procedures of Ablation of Ventricular Tachycardia. (25th August 2016) - DONATEO, PAOLO; BOTTONI, NICOLA; ODDONE, DANIELE; QUARTIERI, FABIO; IORI, MATTEO; MAGGI, ROBERTO; BRIGNOLE, MICHELE
VT Ablation: Introduction: The aim of this study was to assess long‐term results after single and multiple procedures of catheter ablation of ventricular tachycardia (VT). While it is generally accepted that multiple procedures are sometimes necessary in order to achieve long‐term clinical success, the literature on this issue displays wide variability. Methods: We assessed the outcome of 160 consecutive patients who underwent 214 ablation procedures in the period 2008 to May 2015: 93 had overt structural heart disease (SHD) (previous myocardial infarction in 74 cases) and 67 had no SHD. Results: After the first procedure, the 1‐year actuarial recurrence rates were 25% in patients with SHD and 5% in those without. However, recurrences increased progressively after the first year, reaching 46% and 35%, respectively, at 5 years. Overall, VT recurred in 35/93 (38%) patients with SHD and 22/67 (33%) patients without. Redo (1 to 4) procedures were performed in 28 (20%) patients with SHD and 18 (27%) patients without. After the last procedure, the 1‐year actuarial recurrence rates were 5% in patients with SHD and 7% in those without, and the corresponding rates at 5 years were 23% and 7%. During follow‐up, 21 patients died (all in the SHD group): no death was related to VT recurrence. Conclusions: During long‐term follow‐up, VT frequently recurs after the first procedure, both in patients with SHD and in those without; multiple procedures are needed in order to increase the success rate.